PROPHETIC VALUES IN AIK LEARNING (AL-ISLAM AND KEMUHAMADIYAH AT MUHAMMADIYAH HIGH EDUCATION: Case Study at Muhammadiyah University of Purworejo - H Hermawan (Profetika: Jurnal Studi Islam, 2022)
Al-Islam and Kemuhammadiyahan (AIK) must be part of the efforts of Muhammadiyah universities to achieve the vision and mission of Muhammadiyah universities, namely “the formation of human learners who are pious, have a noble character, progress and excel in science and technology as the embodiment of tajdid da’wah amar ma’ruf nahi munkar “. To achieve the stated goals, it is necessary to have comprehensive AIK learning tools and a revolutionary paradigm. One of the ways taken by Muhammadiyah (through the PP Muhammadiyah Higher Education Council) is to create an AIK curriculum that directs students to that goal. Another word for this goal is khoiru ummah which is synonymous with prophetic values. So, in this study, it is studied about how the realization of prophetic values in AIK learning in PTM is and this is what makes the element of novelty in this research. While the purpose of this study was to determine the prophetic values in AIK learning in PTM. This research method uses a qualitative approach, the technique of taking research subjects with purposive sampling, namely at the University of Muhammadiyah Purworejo. While the data was obtained by observation, interviews, and documentation, then data analysis with qualitative descriptive methods, namely: data reduction, data categorization, and synthesis and ended by compiling working hypotheses or drawing conclusions. The results of the research are that the transcendental prophetic value is found in AIK I (creed) courses, the humanization prophetic value is found in AIK II and III courses (worship, morality, muamalah, kemuhammadiyahan), and the value of liberation is found in AIK IV (Islam and science and technology) courses.